2004
DOI: 10.1007/s11661-006-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and texture in Mg-Al-Zn alloys during electron-beam and gas tungsten arc welding

Abstract: The evolution of microstructure and texture in the AZ-series Mg alloys subjected to electron-beam welding and gas tungsten arc welding are examined. Electron-beam welding is demonstrated to be a promising means of welding delicate Mg plates, bars, or tubes with a thickness of up to 50 mm; gas tungsten arc welding is limited to lower-end thin Mg sheets. The grains in the fusion zone (FZ) are nearly equiaxed in shape and ϳ8 m or less in size, due to the rapid cooling rate. The as-welded FZ microhardness and tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The differences in thermal, structural, and electrical properties also lead to differences in solidification microstructure of alloys. [1,2] It has been found that the strength of Mg alloy weldments is much lower than that of the base material and also that the weldability of Mg alloys joined by conventional fusion welding is inferior to that of steel. [1,2] In fusion welds, columnar and equiaxed grains are often the predominant macrostructural constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in thermal, structural, and electrical properties also lead to differences in solidification microstructure of alloys. [1,2] It has been found that the strength of Mg alloy weldments is much lower than that of the base material and also that the weldability of Mg alloys joined by conventional fusion welding is inferior to that of steel. [1,2] In fusion welds, columnar and equiaxed grains are often the predominant macrostructural constituents.…”
Section: Introductionmentioning
confidence: 99%
“…This process leads to solidification in nonequilibrium conditions. It has been reported that rapidly solidified Mg alloys exhibit a change of the microstructure and especially a grain refinement [4], a formation or a modification of the texture [5] and the presence of residual stresses [6].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed descriptions of the experiments can be found elsewhere. 19) Furthermore, the asEBWed samples was subjected to annealing (denoted as the annealed sample) at 350 C for various time durations, resulting in various grain sizes in order to examine the effect of grain size on YS.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Fortunately, it is found that the fine-grained microstructure with weak textures can be produced by electron beam welding (EBW) in the fusion zone (FZ) of EBW magnesium alloys, owing to the high solidification cooling rate inside the fusion zone. 19) In the present paper, the tensile specimens are sampled from the FZ of the EBW AZ31 samples in order to establish the grain size dependence of YS in the randomly textured AZ31 alloy. The results are used as a base to roughly evaluate the influence of texture on grain boundary strengthening in the textured magnesium alloys, which were subjected to various thermo-mechanical processes.…”
Section: Introductionmentioning
confidence: 99%